Calving Dynamics Derived from Satellite Sar Data in Support of Mass Balance Estimations in Lange Glacier, Antarctica - Johnson Gavilan, Erling John; Floricioiu, Dana; Schwalbe, Ellen; Koschitzki, Robert; Maas, Hans-Gerd; Cardenas Mansilla, Carlos Alberto; Cassasa, Gino (My University, 2020)
We present calving flux, calving rate, frontal retreat and volume change rate results in Lange Glacier from 2015 to 2017, including also velocity calculations in 2015, 2017 and 2018. The peak velocities at glacier front were between 1.0 and 1.5 [md-1] near the center line with a maximum frontal retreat of 100 [m]. The glacier presents almost no volume change rate during the period analyzed and the average ice discharge is 0.026 [km3 yr-1].
Keywords: calving flux; calving rate; glacier; ice velocity